THE INFLUENCE OF WORK DISCIPLINE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE - Iis Noviyanti; Lia Asmalah (Asosiasi Dosen Muda Indonesia, 2023)
This study aimed to determine the effect of work discipline on employee performance, Work environment on employee performance and the Effect of Work Discipline and Work Environment on Employee Performance. This study uses a quantitative method by distributing questionnaires to all employees of PT. Eka Mas Republic Branch Tangerang, totaling 71 respondents with saturated sampling technique. The data obtained were then processed using SPSS statistical software version 26. This analysis included validity tests, reliability tests, classic assumption tests, simple regression analysis tests, multiple regression analysis tests, coefficient of determination tests, and statistical tests through t-tests and F tests. The t-test results show that work discipline and work environment partially positively and significantly affect employee performance. The F test simultaneously shows that work discipline and work environment ultimately impact substantially employee performance. The correlation coefficient is 0.926, meaning that the three variables have a firm level of relationship. The R2 value is found to be 0.857, meaning that the influence of work discipline and work environment variables on employee performance is 85.7%, while the remaining 14.3% is explained by other variables not discussed in the study.